Meta-analysis of carcass and meat characteristics of young or super young steers and of different sexual conditions finished in confinement - S. A. Jappe; R. K. Muniz Júnior; J. S. Teixeira; R. F. Pacheco (Boletim de Indústria Animal)
The objective was to evaluate the carcass and meat characteristics of feedlot steers based on sexual condition and age at the beginning of the finishing phase, through a systematic review and meta-analysis. The selection of articles was carried out by two reviewers, who selected articles from the Google Scholar and Scielo platforms. The criteria for choosing articles followed the PICO tool. After searching for articles, they were subjected to analysis under the methodological conditions of the research. After this phase, 61 research articles carried out in Brazil remained, from which information was extracted from the material, methods and results. The data were compared according to the age of the steers: young (between 20 and 26 months of age) and super young (between 10 and 16 months of age); and depending on sexual condition: castrated or not castrated. Young steers have higher slaughter weights and higher hot and cold carcass weights. Meat from super young steers presented a higher score for tenderness when evaluated by the panel of evaluators. Uncastrated steers had higher slaughter weight, hot and cold carcass weight and rib eye area, while castrated steers demonstrated greater thickness of subcutaneous fat in the carcass and meat with higher marbling score. Slaughtering super young and castrated steers improves the quality aspects of the carcass and meat, however it reduces the amount of meat.